DESIGNING AN ENGLISH LANGUAGE SYLLABUS FOR TEACHER EDUCATION PROGRAMS IN INDONESIA - Abid Abid (ELEMENTARY SCHOOL JOURNAL PGSD FIP UNIMED, 2017)
This article aims at describing a sample of a syllabus design for teaching General English at the Department of Primary School Teacher Education in a university in Indonesia. The design is developed within the framework of relevant theories, such as syllabus design, language teaching and assessment. The syllabus focuses on the introduction of English language grammar. It is expected that the design can help the students of the department (henceforth refers to pre-service teachers or PSTs) to prepare themselves when enrolling into other English coursework units in the following semesters, as well as to teach English at the primary school levelin their future career as English language teachers. Keywords: English Language, Syllabus, Teacher Education